Strategie budowania dystansu wobec traumatycznych doświadczeń w autobiograficznej twórczości Artura Sandauera - Koszarska-Szulc, Justyna (Biografie nieoczywiste: Przełom, kryzys, transgresja w perspektywie interdyscyplinarnej, 2018)
The article attempts to analyze the strategy of building a distance to traumatic experiences on the example of Artur Sandauer’s autobiographical works. From the notion of trauma formulated by Zygmunt Freud, we have looked at strategies such as genres entanglement of a work, irony, autotematism, projection of personal experiences to an autobiographical character, use of relations of family members embodied in autobiographical text. The analysis serves to answer the questions whether these strategies allow traumatic events to be worked on, how autobiographical genres can help in this, and whether autobiography can be a source of effort in reconstructing a writer’s biography.